Exploration of combined factors related to quality of life after knee replacement surgery - Kohki Santoh; Hayato Shigetoh; Hiroaki Yamano; Kohtaroh Torizawa; Hiroshi Takasaki; Daisuke Uritani (PLoS ONE, 2025)
In this study, we aimed to identify combined factors associated with lower postoperative quality of life (QOL) in knee replacement (KR) patients, utilising data from the Osteoarthritis Initiative (OAI) database. The data of 44 individuals from the OAI who underwent KR surgery was included in this study. Preoperative baseline data, including demographic information, comorbidities, depressive symptoms, knee-joint symptoms, and health-related QOL, were analysed using association rule analysis to identify single and combined factors linked to low postoperative QOL that were assessed with Short Form-12. Preoperative factors such as comorbidities, high Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)-pain scores, poor physical function, and older age were strongly associated with lower postoperative physical component scores (PCS) at 2 years. When combined, these factors showed even stronger associations with lower PCS. No significant associations were found with PCS and mental component scores (MCS) at 1 and 2 years postoperatively. Our findings emphasize the importance of evaluating combined preoperative factors, including comorbidities, pain levels, physical function, and age, as they may be associated with lower postoperative QOL in patients who underwent KR. Considering combined factors, rather than assessing single factors in isolation, may provide a more appropriate understanding of postoperative outcomes.